Intravenous bolus somatostatin after diagnostic cholangiopancreatography reduces the incidence of pancreatitis associated with therapeutic endoscopic retrograde cholangiopancreatography procedures: a randomised controlled trial. Issue 12 (21st November 2003) - Poon, R T-P; Yeung, C; Liu, C-L; Lam, C-M; Yuen, W-K; Lo, C-M; Tang, A; Fan, S-T
Abstract : Background: Previous studies suggested that somatostatin given before endoscopic retrograde cholangiopancreatography (ERCP) may reduce the incidence of post-ERCP pancreatitis. However, the routine use of somatostatin in all patients undergoing ERCP is not likely to be cost effective. This study evaluated whether intravenous bolus somatostatin given after diagnostic cholangiopancreatography could reduce the incidence of pancreatitis in a group of patients undergoing therapeutic ERCP procedures. Methods: In a randomised, double blind, controlled trial, the effect of intravenous bolus somatostatin 250 μg given immediately after diagnostic cholangiopancreatography was compared with that of placebo in patients who required endoscopic sphincterotomy or other therapeutic procedures. The primary end point was the incidence of post-ERCP clinical pancreatitis, and a secondary end point was the incidence of hyperamylasemia. Results: A total of 270 patients were randomised. The somatostatin group (n = 135) and the placebo group (n = 135) were comparable in age, sex, indications for treatment, and types of procedure. The frequencies of clinical pancreatitis (4.4% v 13.3%; p = 0.010) and hyperamylasemia (26.0% v 38.5%; p = 0.036) were both significantly lower in the somatostatin group compared with the placebo group. Conclusions: A single dose of intravenous bolus somatostatin, given immediately after diagnostic cholangiopancreatography, is effective in reducing the incidence of pancreatitis after therapeutic ERCP. This novel approach of administering prophylactic somatostatin may offer a cost effective prophylaxis for post-ERCP pancreatitis.